KRITIK NARASI MISOGINIS: Analisis Pemikiran Fatima Mernissi tentang Hadis dan Kuasa Perempuan - Millat Ahmad, Nehru; Anam, Saichul; Rohadatul Aisyi, Hithna (Jurnal Studi Islam dan Sosial, 2025)
This study examines Fatima Mernissi's thoughts on misogynistic hadiths and their relevance to women's leadership in the context of Islam. Mernissi, as a feminist thinker, challenged traditional interpretations of hadith that were considered degrading to women, as she stated in her book "Women and Islam: A Historical and Theological Enquiry." Mernissi argues that there is a defect in the hadith because its message contradicts common sense, particularly in sidelining the role of women as leaders and failing to provide public breadth. Departing from this reasoning, she criticized hadiths with misogynistic undertones concerning their narrators and meanings. This study employs a qualitative approach that includes descriptive analysis and the figure study method. From the results of this research, the author identified two major points in Fatima Mernissi's thought: First, she analyzes the text of the hadith using a historical and methodological approach. Second, the methodology that Mernissi applies is based on Ulūm al-Ḥadīth, which aids her in refuting misogynistic hadiths. She does this when determining whether to accept or reject a hadith. Regarding the understanding of hadith, Mernissi applies a historical approach.